All‐Inorganic Perovskite Quantum Dots/p‐Si Heterojunction Light‐Emitting Diodes under DC and AC Driving Modes. Issue 2 (4th December 2017) - Liu, Jingjing; Sheng, Xuexi; Wu, Yangqing; Li, Dongke; Bao, Jianchun; Ji, Yang; Lin, Zewen; Xu, Xiangxing; Yu, Linwei; Xu, Jun; Chen, Kunji
Abstract: Light‐emitting diodes based on perovskite quantum dots have attracted much attention since they can be applied in low‐cost display, biosensors, and other optoelectronic devices. Here, all‐inorganic light‐emitting diodes based on n‐type perovskite quantum dots/p‐Si heterojunction are fabricated. Both the green and the red light emission are achieved at room temperature. The output power density is 0.14 mW cm −2 for green light device and 0.25 mW cm −2 for the red one. The relatively low turn on voltage and high emission intensity in red light device can be attributed to the small hole injection barrier between CsPbI3 quantum dots and p‐Si. The emission drop off at high current density is observed under direct current (DC) driving mode, which is significantly improved by applying alternating current (AC) square pulses. The enhanced electroluminescence and the improved operation stability at high current density under AC driving mode can be attributed to the less thermal degradation and the reduced charge accumulation in the interface defect states due to the alternated biases. The results demonstrate the possibility of integrating the perovskite quantum dots with Si platform, which will be helpful to extend their actual applications. Abstract : All‐inorganic light‐emitting diodes based on n‐type perovskite quantum dots/p‐Si heterojunction are fabricated. Both the green and the red light emission are achieved at room temperature. The enhanced electroluminescence and improved operation stability under alternating current driving mode can be attributed to the less thermal degradation and the reduced charge accumulation in the interface defects states due to the alternated biases.